2007
DOI: 10.1007/s10653-007-9081-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme activities of Microcystis aeruginosa in response to nonylphenols and degradation of nonylphenols by M. aeruginosa

Abstract: The aim of this study was to examine the effects of chemical nonylphenols (NPs) on the antioxidant system of Microcystis aeruginosa strains. The degradation and sorption of NPs by M. aeruginosa were also evaluated. High concentrations of NPs (1 and 2 mg/l) were found to cause increases in superoxidase dismutase (SOD) and glutathione-S-transferase (GST) activities and in glutathione (GSH) levels. These results suggest that toxic stress manifested by elevated SOD and GST levels and GSH contents may be responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…A similar cell response was also observed in Microcystis aeruginosa and Chlorella species after NP exposure [38,39,40], and Chlorella fusca , Monoraphidium braunii and Stephanodiscus hantzschii after bisphenol-A (BPA) exposure [41,42,43]. The chlorophyll a curves showed that the A. acicularis , C. minutus and S. quadriauda had negative growth under 2.0–2.5 mg·L −1 NP exposure, whereas the C. vulgaris still grew well (Figure 1).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A similar cell response was also observed in Microcystis aeruginosa and Chlorella species after NP exposure [38,39,40], and Chlorella fusca , Monoraphidium braunii and Stephanodiscus hantzschii after bisphenol-A (BPA) exposure [41,42,43]. The chlorophyll a curves showed that the A. acicularis , C. minutus and S. quadriauda had negative growth under 2.0–2.5 mg·L −1 NP exposure, whereas the C. vulgaris still grew well (Figure 1).…”
Section: Discussionsupporting
confidence: 68%
“…Such A. acicularis , C. vulgaris and S. quadriauda biodegradation was much faster than the previous results from two M. aeruginosa strains, which exhibited more than 60% NP degradation after 12 days of incubation, with different concentrations of NP [38] and microalgal species from other taxa [34]. These findings suggested that potential use of A. acicularis , C. vulgaris and S. quadriauda in the treatment of waste water containing the compound.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, internalisation of NP, followed by formation of another sub-product (which could not be measured in this study) probably took place. This result is very different from that reported by Wang and Xie [18] for M. aeruginosa binding of NP, at concentrations from 0.09 to 9 μM, who have found binding as high as 61% of the compound. Even so, results similar to ours have been reported in another work in which the amount of oestrogen that partitioned to the algae Chlorella vulgaris did not exceed 9% of the total [3].…”
Section: Resultscontrasting
confidence: 99%
“…Wang and Xie [18] have found that NP at concentrations ranging from 4.5 to 9.0 μM was biotically removed from cultures of M. aeruginosa by glutathione conjugation. We can hypothesise, but not prove using our data, that a similar mechanism might occur when M. aeruginosa was exposed to the lower NP concentrations used in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant enzyme GST is involved in the degradation of exogenous chemicals in microalgae, which could catalyze the conjugation of exogenous chemicals with glutathione [41]. For instance, Wang and Xie [42] observed the contribution of elevated GST activity to the biodegradation of nonylphenol in M. aeruginosa. In the present study, elevated GST activity was also coupled to the degradation of amoxicillin.…”
Section: Discussionmentioning
confidence: 99%